2016
DOI: 10.1002/hyp.11085
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium‐excess determination of evaporation to inflow ratios of an alpine lake: Implications for water balance and modeling

Abstract: The numerous lakes on the Tibetan Plateau play an important role in the regional hydrological cycle and water resources, but systematic observations of the lake water balance are scarce on the Tibetan Plateau. Here, we present a detailed study on the water cycle of Cona Lake, at the headwaters of the Nujiang‐Salween River, based on 3 years (2011–2013) of observations of δ18O and δ2H, including samples from precipitation, lake water, and outlet surface water. Short‐term atmospheric water vapor was also sampled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 68 publications
3
32
0
Order By: Relevance
“…Figure presents the calculated E/I as a comparison with the estimated annual mean E/I values (dashed lines). Annual mean E/I calculated from both δ 18 O and δ 2 H in the 3 years were 0.23, 0.25, and 0.27, close to the results from deuterium excess‐based estimation (Cui et al, ). δ 18 O‐ and δ 2 H‐based E/I were very similar with a mean difference of 0.01.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…Figure presents the calculated E/I as a comparison with the estimated annual mean E/I values (dashed lines). Annual mean E/I calculated from both δ 18 O and δ 2 H in the 3 years were 0.23, 0.25, and 0.27, close to the results from deuterium excess‐based estimation (Cui et al, ). δ 18 O‐ and δ 2 H‐based E/I were very similar with a mean difference of 0.01.…”
Section: Resultssupporting
confidence: 82%
“…A sampling location on the steep west bank was selected for ease of access and to avoid potential for incomplete mixing related to surface stream inlets. The isotopic composition of surface lake water in this study was found to be consistent with that of outlet water and central lake water, indicating that the west bank location was fairly representative of lake‐average isotopic composition under well‐mixed conditions (Cui et al, ). In total, there were 110 surface lake samples collected on the west bank from June 2011 to December 2013.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations